Pengintegrasian Literasi Humanis dalam Pembelajaran bagi Guru-guru SMPN 2 Dumai Timur - Asnawi Asnawi; Sri Wahyuni; Alber Alber; Noni Andriyani; Fauzul Etfita (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2022)
The integration of humanist literacy in learning materials is a competency that must be possessed in facing future challenges. This competence involves a person's humanist receptive skills to social symptoms and practices in society. There are many social practices of the community that exist in social life and an in-depth study is needed to fortify the humanist values ​​of students. The fundamental problem that is currently happening is the erosion of the humanist values ​​of students due to the flow of globalization culture. Therefore, teachers need to update the design of digital-based teaching materials in learning. It aims to communicate, collaborate, and reflect on human values ​​to students digitally. That way students can make wise decisions about human values ​​in the learning process. This dedication target is carried out for teachers of SMPN 2 Dumai Timur. The purpose of this service is to provide an update on the design of digital-based teaching materials and the integration of humanist literacy. The solution to this problem is to conduct training for the teachers of SMPN 2 Dumai Timur on the integration of humanist literacy in learning materials. The benefit of this service is that teachers can integrate humanist literacy in learning materials.